Suicidal Emotions, Motivations and Rationales in Australian Men: A Qualitative Exploration - Diane Macdonald; Ally Nicolopoulos; Stephanie Habak; Helen Christensen; Katherine Boydell (SAGE Publishing, 2024)
Suicide has a devasting and far-reaching effect on our communities. In developed countries, most people who die by suicide are male. Understanding men's mental health and what they experience in a suicidal state is key to preventing future attempts. Our paper explores how a group of 37 men in Australia describe the leadup to their suicidality. Underpinned by interpretive phenomenological analysis, interview transcripts were examined for phrases that the investigative team subjectively identified as profound. Our approach considered language and expression that evoke reactions to the sometimes contradictory nature of suicide. The process enabled our team to identify the emotions, rationales, and motivations for and against suicide that give rise to and arise during suicidal states. One man's source of strength may be another's cause of anguish, so any single, one-size-fits-all pathway to suicide prevention is unlikely to succeed, signaling the need for a tailored approach to suicide prevention.